Pijlen van naamloze liefde : pioniers van de homo-emancipatie. - Hafkamp, Hans; van Lieshout, Maurice (Amsterdam : SUA, 1988)
Fonds Suzan Daniel (FSD)
Fonds Suzan Daniel (FSD)F/97/008
Nederlands
Monografie